Power Transmission for Millimeter-Wave Indoor/Outdoor Wearable IoT Devices Using Grounded Coplanar Waveguide-Fed On-Body Antenna - Fuad Erman; Slawomir Koziel; Alhareth Zyoud; Leifur Leifsson; Ubaid Ullah; Shaker Alkaraki (IEEE Access)
This paper presents for the first-time evaluation of wireless power transmission (WPT) for sustainable low-powered Internet of Things (IoT) devices in realistic indoor/outdoor scenarios using empirical propagation models at 28 GHz. The used empirical propagation models have shown that using an on-body $9× 9$ mm-wave rectenna array based on a proposed mm-wave antenna is able to charge IoT devices at a distance of 57 m for line-of-sight (LOS) indoor temporal environment, and at a distance of 10 m for LOS outdoor tropical propagation model using a base station with 53 dBm transmission power. Furthermore, the mm-wave on-body $9× 9$ rectenna array occupies an area equal to that of a single UHF rectenna, while collecting 17-fold more power. In addition, the article discusses the design and experimental results of a single-element on-body mm-wave antenna used to design the $9× 9$ rectenna array. The proposed mm-wave antenna is a single-layer low-profile structure. Furthermore, the antenna has a stable gain of over 9.5 dBi and a wide beamwidth. The on-body antenna structure consists of rectangular multi-slot patch fed by a $50~Ω $ grounded coplanar waveguide (GCPW) line. Employing the multi-slot configuration results in a wearable antenna’s impedance bandwidth of 3.73 GHz. The peak measured gain of the antenna is 10.5 for chest/arm-mounted case in the operating 28 GHz N257 5G band. The antenna’s radiation pattern forms a wide off-body forward direction beam. A prototype of the proposed antenna is fabricated and validated experimentally for both cases on a human volunteer arm/chest and in the free space. The size of the proposed structure is small and can collect power with high efficiency due to the short wavelength of millimeter wave (mm-wave) in contrast to UHF antennas.